Knowledge and Readiness of Primary Teachers on School Based Assessment An Exploratory Study - Roy, M.M.; Sehrawat, Meena; Dabas , Ritika (JOURNAL OF INDIAN EDUCATION, 2022)
In Delhi, primary teachers from the South Delhi Municipal Corporation of Delhi attended NISHTHA training conducted by SCERT, Delhi, for five days. Teachers attended different training schedules conducted from November 2019 to February 2020. Teachers completed various training modules, of which one module was on school-based assessment (SBA). After the completion of the training, it was necessary to follow up the classroom practices of the teachers in terms of knowledge and readiness about SBA. Two research questions were proposed to elicit information about teachers’ knowledge and readiness. The research study used a qualitative research method to answer the research questions, and data were collected from 10 primary school teachers in District South West B, who were selected through purposive sampling and were interviewed. Findings showed that teachers still require SBA training and this becomes very essential for the present time in which we are to implement and achieve the goal of foundational literacy and numeracy. So, effective training sessions may be able to meet their requirements. Procedural knowledge training on SBA has the potential to provide the necessary skills and competence for them to deal with the issues and processes that they will encounter while implementing SBA.